Forensic Analysis of Abortion Trends: A Study of Gestational Data (Journal of Current and Advance Medical Research, 2025)
Background: Abortion is a public health issue.Objective: This study was aimed to assess the pattern of abortion among women in Dhaka city, focusing on demographics, reasons for seeking abortion, and the treatment methods utilized.Methodology: This cross-sectional study was conducted from January to March 2024, focusing on 38 women who experienced abortion at a tertiary hospital in Dhaka to assess the pattern of abortion. Utilising a convenient non-probability sampling technique, data were collected through face-to-face interviews using a pretested and modified questionnaire designed to meet the study's objectives. Descriptive statistics were calculated to analyze the data.Results: The findings revealed that 31.6% of women completed their Secondary School Certificate and 23.7% had no formal education and 71.1% identified as housewives. Gravida status showed diversity in reproductive experiences, with 34.2% having three pregnancies. Alarmingly, 63.2% categorised their pregnancies as unwanted. Only 21.1% reported using contraception. Treatment methods predominantly included Dilation and Curettage (50%).Conclusion: In conclusion, this study underscores the urgent need for enhanced reproductive health education and resources to empower individuals to make informed decisions and reduce unwanted pregnancies.Journal of Current and Advance Medical Research, January 2024;11(1):3-7